Compensatory muscle activation and spinal curve changes in response to fatigue among adolescent male athletes - Gál-Pottyondy, A.; Petró, B.; Takács, M.; Négyesi, J.; Nagatomi, R.; Kiss, R. M. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The prone plank test has been often used to assess the strength and endurance of trunk muscles. We aimed to develop a new measurement protocol to objectively monitor the changes in spinal curves and muscle activity simultaneously.